THE EFFECT OF MUSCLE BALANCE EXERCISES ACCORDING TO SOME BIOMECHANICAL VARIABLES, THE ELECTRICAL ACTIVITY OF THE THIGH MUSCLES, AND THE ACHIEVEMENT OF THE LONG JUMP YOUTH - Dr. Ahlam Sadiq Hussain (Galaxy International Interdisciplinary Research Journal, 2023)
The developments that took place in the field of sports training science are many and significant at the theoretical and practical levels as a result of scientific and practical experiments and research that are still continuing in the use of various training methods and methods that contribute to the development of the level of players, and that this development comes from the work of the corresponding working muscles through the contraction of a muscle or A group of muscles on the same joint while the opposite is relaxed so as not to hinder movement. Therefore, training to develop strength and mechanical variables for long jump players requires work to balance force on one joint, which called the researcher to study this problem. The study aimed to prepare exercises for muscle balance and to know the effect of this Exercises in some biomechanical variables, electrical activity of the thigh muscles, and the achievement of the long jump for young people, and there were differences with a statistically significant difference between the pre and post tests of the research variables. For muscles, the researcher concluded the contribution of exercises in making a difference to Some biomechanical variables and the electrical activity of the muscles. He studied other variables of the electrical activity of the muscles, such as the arena and other games.